Risk Factors that Predict Future Onset of Each DSM-5 Eating Disorder: Predictive Specificity in High-Risk Adolescent Females - Stice, Eric (J Abnorm Psychol, 2016)
OBJECTIVE: Because no single report has examined risk factors that predict future onset each type of eating disorder and core symptom dimensions that crosscut disorders, we addressed these aims to advance knowledge regarding risk factor specificity. METHOD: Data from 3 prevention trials that targeted young women with body dissatisfaction (N=1272; M age 18.5, SD 4.2) and collected annual diagnostic interview data over 3-year follow-up were combined to identify predictors of subthreshold/threshold anorexia nervosa (AN), bulimia nervosa (BN), binge eating disorder (BED), and purging disorder (PD). RESULTS: Negative affect and functional impairment predicted onset of all eating disorders. Thin-ideal internalization, body dissatisfaction, dieting, overeating, and mental health care predicted onset of subthreshold/threshold BN, BED, and PD; positive thinness expectations, denial of cost of pursuing the thin ideal, and fasting predicted onset of 2 of these 3 disorders. Similar risk factors predicted core eating disorder symptom onset. Low BMI and dieting specifically predicted onset of subthreshold/threshold AN or low BMI. Only a subset of factors showed unique predictive effects in multivariate models, likely due to moderate correlations between the risk factors (M r = .14). CONCLUSIONS: Results provide support for the theory that pursuit of the thin ideal and the resulting body dissatisfaction, dieting, and unhealthy weight control behaviors increase risk for binge/purge spectrum eating disorders, but suggest that youth who are inherently lean, rather than purposely pursuing the thin ideal, are at risk for AN. Impaired interpersonal functioning and negative affect are transdiagnostic risk factors, suggesting these factors should be targeted in prevention programs.